Awareness and Preventive Practices regarding Pneumonia among Mothers’ of under 5 Year Children in Surkhet, Nepal - Bhandari, Bhawana; Thapa, Sapana; Ojha, Anil Babu; Dangi, Pratikshya (AMC Multidisciplinary Research Journal, 2025)
Pneumonia has become one of the major common health problem among children under five years of age. Pneumonia accounts for 19% of all under-five deaths worldwide. Around 6.5 million deaths of under five children are due to Pneumonia. To assess the Awareness and Preventive Practice regarding Pneumonia among Mother’s of under 5 year Children. Descriptive, cross-Sectional study was adopted for the study.172 samples were selected by using purposive non probability sampling technique. Self developed semi-structured questionnaire was used to collect data through interview technique. Data analysis was done in SPSS version 20. Descriptive and inferential statistics was used to analyze the data. It showed that 52 (49.5%) respondents had adequate level of awareness and 53 (50.5%) respondents had moderate level of awareness about Pneumonia. Regarding preventive practice 101(96.2%) respondents had always consulted their doctors when their child had cough 104(99%) of respondents visited doctor only when symptoms arise,104 (99%) respondents practiced honey water to relieve cough. 96 (91.4%) of respondents took their children to private hospital for treatment, (96.2%) believed healthy diet as a preventive measure, physical activity, sanitation and vaccination could prevent pneumonia which accounts 60 (57.1%), 88 (83.8%) and 49 (46.7%) respectively ,93(88.6%) respondents keep children in room with doors closed to kept the room warm ,12(11.4%) respondents kept room with open windows and doors to help a sick child at home. Also, 101(96.2%) respondents used cold sponge to reducing fever when the child has pneumonia, 105(100%) respondents kept children aware from crowded place to prevent child from dust allergy followed by using masks (97.1%). Half of the respondents had high level of awareness about pneumonia and half of them had low level of awareness. There was no any association found between awareness level and socio- demographic variables.